2005
DOI: 10.1128/aem.71.10.6260-6266.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Proteolytic System ofLactobacillus sanfranciscensisDSM 20451Tduring Growth in Sourdough

Abstract: Protein hydrolysis and amino acid metabolism contribute to the beneficial effects of sourdough fermentation on bread quality. In this work, genes of Lactobacillus sanfranciscensis strain DSM 20451 involved in peptide uptake and hydrolysis were identified and their expression during growth in sourdough was determined. Screening of the L. sanfranciscensis genome with degenerate primers targeting prt and analysis of proteolytic activity in vitro provided no indication for proteolytic activity. Proteolysis in asep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 37 publications
4
51
0
Order By: Relevance
“…In the present study, no expression of the only proteinase represented on the microarray was found, namely, of the cell wall-associated serine proteinase gene. This confirmed that proteinase activity might not be of utmost importance for the microbiota present, as a sufficient amount of peptides is already generated by the action of flour proteinases (65,76). However, the LAB functional gene microarray did not contain oligonucleotides targeting this gene in L. plantarum or L. fermentum, and so no clear conclusion can be drawn regarding the importance of extracellular proteolytic activity for competitiveness, although strains of these species elaborating proteinase activities have been isolated from sourdough (14,21).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the present study, no expression of the only proteinase represented on the microarray was found, namely, of the cell wall-associated serine proteinase gene. This confirmed that proteinase activity might not be of utmost importance for the microbiota present, as a sufficient amount of peptides is already generated by the action of flour proteinases (65,76). However, the LAB functional gene microarray did not contain oligonucleotides targeting this gene in L. plantarum or L. fermentum, and so no clear conclusion can be drawn regarding the importance of extracellular proteolytic activity for competitiveness, although strains of these species elaborating proteinase activities have been isolated from sourdough (14,21).…”
Section: Discussionsupporting
confidence: 57%
“…In general, peptides present in a food matrix (e.g., milk) are taken up by LAB and are degraded intracellularly (38). The resulting amino acids may be used for biosynthesis or other metabolic activities (12,17,65). In the case of sourdough LAB, in particular, it has been shown that accumulated amino acids that are not further metabolized, such as phenylalanine, are transported out of the cell (66).…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected by the considerable levels of maltose retrieved after each fermentation step and an increase of total amino acids upon fermentation (27,39,40,69). The present study showed that the competitiveness of sourdough LAB is enhanced by both the use of the arginine deiminase pathway (in an early stage) and the use of alternative electron acceptors.…”
Section: Discussionmentioning
confidence: 65%
“…Lactic acid bacteria (LAB) and yeasts play a key role in sourdough fermentation processes (9,21,26,28,29,55). Sourdough LAB have been intensively studied with respect to their carbohydrate metabolism (16,24,60), proteolysis and amino acid metabolism (16,23,58,69), lipid metabolism (16), and production of volatile compounds (7,31,32). Besides these general metabolic traits, specific metabolic properties have been recognized in sourdough LAB, such as the use of alternative electron acceptors (59, 61), the production of antifungal compounds (38,45,57), the biosynthesis of exopolysaccharides (36, 63, 64), and arginine catabolism (8, 53).…”
mentioning
confidence: 99%
“…4) (69). Extracellular protease activity is required for growth in milk but not for growth in other substrates (68,70,71). Accordingly, the gene coding for the extracellular protease PrtH was frequently found in dairy isolates of the L. delbrueckii, L. casei, L. salivarius, and L. buchneri groups but was rarely present in other lactobacilli.…”
Section: ϫ4mentioning
confidence: 99%